The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.11648/j.es.20190402.12
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Physical Properties of PP and HDPE

Abstract: The properties of these polymers, as in the case of any materials, depending on the molecular weight of the polymer and the structure of the polymer chains. The main objective of this work is to study the mechanical and physical properties of pure PP and HDPE. To obtain a full characterization of pure polymer, samples were produced using a compression molding technique. Polymeric samples successfully filled the cavity of the die. The mechanical properties of PP and HDPE were determined using three-point bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The results show HDPE fibers with a low water absorption percentage of around 0.255%, due to the hydrophobic nature of the HDPE fibers, and some material micro-cracks, and the HDPE recycled fibers' density is 0.955 g/cm 3 . These results are similar to those reported in the literature [22,33,37]. In Figure 3, the HDPE recycled fibers' direct stress-strain curve is observed, and the data on the mechanical properties are shown in Table 2.…”
Section: Physical and Mechanical Tests Of The Hdpe Fiberssupporting
confidence: 90%
See 1 more Smart Citation
“…The results show HDPE fibers with a low water absorption percentage of around 0.255%, due to the hydrophobic nature of the HDPE fibers, and some material micro-cracks, and the HDPE recycled fibers' density is 0.955 g/cm 3 . These results are similar to those reported in the literature [22,33,37]. In Figure 3, the HDPE recycled fibers' direct stress-strain curve is observed, and the data on the mechanical properties are shown in Table 2.…”
Section: Physical and Mechanical Tests Of The Hdpe Fiberssupporting
confidence: 90%
“…Five samples, thirty fiber pieces each, were water-saturated for 24 h and weighed using a Denver Instrument 0.0001 g precision electronic balance. Samples were deposited in 50 mL probes, and distilled water was poured in a 30 mL gauge and calculated according to the ASTM D792 standard [32] using the following Equation (2) [33,34]:…”
Section: Physical and Mechanical Properties Of The Fibersmentioning
confidence: 99%
“…Upon addition of PP, the Young's modulus and yield strength increased, but elongation at break and impact strength decreased. Hassan Awad et al [198] observed similar tensile property trends in rPP/rHDPE blends upon rPP addition. The crystallisation behaviour of PO blends is also affected by the recycling process.…”
Section: Composition Of Rpe and Rpp Blendsmentioning
confidence: 76%
“…Finally, the results of Table 1 indicate that the T1 composite exhibited the highest resistance to deformation under tensile load, indicative of HDPE’s ductile nature [ 63 ]. Conversely, PP’s inclusion tends to reduce the material’s plasticity, making it more prone to deformation at lower loads due to its inherent brittleness.…”
Section: Resultsmentioning
confidence: 99%